A Review on Structured Scheme Representation on Data Security Application - Siti Norussaadah Mohd Salleh; Roshidi Din; Nur Haryani Zakaria; Aida Mustapha (Institute of Advanced Engineering and Science, 2018)
With the rapid development in the era of Internet and networking technology, there is always a requirement to improve the security systems, which secure the transmitted data over an unsecured channel. The needs to increase the level of security in transferring the data always become the critical issue. Therefore, data security is a significant area in covering the issue of security, which refers to protect the data from unwanted forces and prevent unauthorized access to a communication. This paper presents a review of structured-scheme representation for data security application. There are five structured-scheme types, which can be represented as dual-scheme, triple-scheme, quad-scheme, octal-scheme and hexa-scheme. These structured-scheme types are designed to improve and strengthen the security of data on the application.